Edukasi Publik Melalui Museum Mini dan Pameran Sejarah Lokal di Sekolah dan Desa - Dokolamo, Hamid; Ima, Wa; Kissiya, Efilina (Jurnal Pengabdian Arumbai, 2026)
This community service program was initiated to address the low level of historical awareness in island communities rich in local artifacts and narratives but underutilized in education. The purpose was to foster collaboration between schools and communities in preserving local history through the development of a mini museum and traveling exhibition titled “Tracing the History of the Small Islands of Maluku.” The method employed a participatory approach, field observation, co-design workshops, guide training, and mixed-method evaluation under a reflective action framework. Findings indicated a 32% increase in students’ historical awareness and greater community participation in cultural preservation. The mini museum and mobile exhibition proved effective as educational media and cultural identity enhancers. The program introduced an innovative community-based cultural engagement model applicable to other island regions. It implies the integration of local history into curricula and promotes sustained collaboration among universities, schools, and communities